Sustainable inclusion of smallholders in the emerging high quality cassava flour value chains in Africa: challenges for agricultural extension services - Adebayo, K.; Abayomi, L.; Abass, A.; Dziedzoave, N.T.; Forsythe, L.; Hillocks, R.J.; Gensi, R.; Gibson, R.; Graffham, A.J.; Ilona, Paul; Kleih, Uli K.; Lamboll, R.I.; et al. (2010)
Based on the premise that smallholders often get excludedas markets become more commercial, this paper draws lessons from the Cassava: Adding Value for Africa (C:AVA) Project by exploring the main issues and challenges facing extension service partners in five African countries (Nigeria, Ghana, Tanzania, Ugandaand Malawi). These lessons include issues around competiveness in the supply of raw material, assisting smallholders to produce value-added products competitively, working with a range of partners at different stages in the value chain to take pilot studies to scale, ensuring and maintaining quality, selecting appropriate technologies for different circumstances, anticipating negative effects of the market environment on smallholders and ensuring that strategies for ensuring benefits for women and other disadvantaged groups are incorporated into extension service operations. It concluded that one strategy does not work in all countries and, while positive government support for cassava development is helpful, the real challenge is in the need to target markets according to realisable capacities of the smallholder actors in the value chain.